Islam and tolerance: an overview of some discourses on tolerance and intolerance of Islam - Muhamad Shukri, Abdul Salam (Command Ground Publishing Pty Ltd, 2008)
It should be pointed out that on the issue of Islam and Tolerance, there are countless works, papers and articles that have been written on it. However, what this paper intends to do is to simply highlight the trends of thought on the issue as may be relevant to its own discourse, and not to go into it in full details. In the light of this, the questions that this paper seeks to find answer to, are hat is the conception of tolerance in Islam? Does Islam as a religion emphasises tolerance? What are the precedents of Islam concerning the issue of tolerance and many more? On the issue of Islam as a religion of tolerance or intolerance, this paper identified two main trends of thought on Islam from discourses, namely Islam is religion of tolerance and of intolerance. Another trend of thought is reconciliation between the two opposite views the basis that Islam as religion is in line with tolerance in theory and practice. It was also found that the issue of intolerance was not limited to the Islamic religion alone, but it cut across all religions and civilisations and even in the present era. The problem of intolerance was revolved around the reader of a religious text who determines the kind of readings, meanings and interpretation that is given to the text.